2019
DOI: 10.30534/ijatcse/2019/83832019
|View full text |Cite
|
Sign up to set email alerts
|

Application of Pressure Biofeedback Unit as Part of Ergonomics Assessment Tools for Assessing Back Pain among Computer Users

Abstract: The decrease in the back muscle strength, especially Transverse Abdominus (TrA) muscle can be an early symptom for the occurrence of back pain among individual. The Pressure Biofeedback Unit (PBU) was frequently used in the clinical setting to assess the TrA strength level among back pain patients. However, in the ergonomics setting, lack of studies available to look into the usefulness of the PBU to assess the back muscle strength level, especially the TrA among the working population who are having back pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…However most of the research is carried out by measuring muscle activity using EMG sensor. The EMG is broadly used in detecting muscle electrical signal [27], in many field such as biomedical [28], sports sciences [13,29,30], rehabilitation [31] and commonly in ergonomics [32]. Study in [1] and [25] have reported that high performance of archer attained at less muscles activity in modern archery.…”
Section: Introductionmentioning
confidence: 99%
“…However most of the research is carried out by measuring muscle activity using EMG sensor. The EMG is broadly used in detecting muscle electrical signal [27], in many field such as biomedical [28], sports sciences [13,29,30], rehabilitation [31] and commonly in ergonomics [32]. Study in [1] and [25] have reported that high performance of archer attained at less muscles activity in modern archery.…”
Section: Introductionmentioning
confidence: 99%